Tale of a tadpole - Wallace, Karen (New York : DK Pub., 1998)
Describes the development of a tadpole.
"Preschool-Grade 1.".
Wilson's Children, October 2006.
School Library Journal, April 1999.
Wilson's Children.
School Library Journal.
2.5
Keywords: Tadpoles -- Juvenile literature; Frogs; Frogs; Tadpoles; Readers (Elementary)